Infections in diabetics: a ten-year analysis on hospital discharge records in an Italian region. (30th September 2020) - Meo, F; Di Giovanni, P; Cedrone, F; D'Addezio, M; Di Martino, G; Masciarelli, M; Scampoli, P; Staniscia, T
Abstract: Background: Patients with diabetes mellitus (DM) have increased risk of developing infections and complications from infections that require hospitalization and greater healthcare utilization. This study aimed to analyze hospitalizations in DM patients with a diagnosis of infection and to assess the burden of infections on the regional healthcare system in terms of length of stay and in-hospital mortality. Methods: A retrospective cross-sectional study was performed from 2006 to 2015 in Abruzzo, an Italian region. Data were collected from hospital discharge records (HDRs) of patients with a diagnosis of DM. All the admissions with an ICD-9 infection diagnostic code were identified. Logistic regression models were implemented to evaluate the association between infections and the study outcomes. Results: A total of 182, 709 HDRs of DM patients were identified, 12, 381 (6.78%) of which related to an infectious disease. The number of admissions with a diagnosis of infection increased during the study period (+4.0%). Respiratory infections were the most common (69.8%), followed by sepsis (9%), and skin and soft tissue infections (8.7%). Factors associated with the infection were age<18 (aOR=1.88; 95%CI:1.42-2.47), age≥65 (aOR=1.29; 95%CI:1.23-1.35), and DM type 2 (aOR=1.19; 95%CI:1.12-1.26). Diabetic patients with an infectious disease had a longer median length of stay (days:10; IQR:6-16) than those without infections (days:7; IQR:3-12) (p < 0.001), and showed higher in-hospital mortality (aOR=2.67; 95% CI:2.5-2.8). Conclusions: Over the study period, hospitalizations related to infections among diabetics rose. The increase was registered mostly among the youngest and the oldest subjects. Infectious disease diagnosis was associated with longer length of stay and higher in-hospital mortality. Cost-effective strategies for infection prevention in patients with DM are needed in order to reduce morbidity and the impact of these conditions on the healthcare system. Key messages: Patients with diabetes have increased risk of developing infections. In our study, infectious disease diagnosis was associated with longer length of stay and higher in-hospital mortality. Cost-effective strategies for infection prevention in patients with diabetes are needed in order to reduce morbidity and the impact of these conditions on the healthcare system.